Optimalisasi Sistem Angkutan Sampah di Kelurahan Pulau Setokok dengan Pemanfaatan Sistem Informasi Geografis (SIG) - Farouki Dinda Rassarandi; Oktavianto Gustin; Rizki Widi Pratama; Zara Azhari; Laras Dwi Ramdanni; Moh Bagus Rahmadi; Karisma Pratama Ramadhan; Nurhadi Bashit (Journal of Science and Applicative Technology, 2023)
The increasing population in Pulau Setokok Village has led to an increase in the waste generation which is not supported by the availability of representative TPS. In addition, the weak waste management system also makes this issue a major problem in the area. One of the important aspects in waste management on Setokok Island is the waste transportation system. The purpose of this study was to determine the location of alternative TPS in Pulau Setokok Village based on SNI No.19-3241-1994, analyze the suitability of the existing TPS in Pulau Setokok Village based on the SNI and optimize the waste transportation system from the existing TPS in Pulau Setokok Village to the nearest TPA with apply Network Analysis GIS. The determination of the recommended location for the TPA in the Pulau Setokok Village in this study was technically determined from the highest score of the feasible zone at the allowance stage, where it was found that the highest score in the allowance stage was 282, covering an area of ​​2.1 Ha, which is relatively in the middle of Setokok Island which is crossed by the Trans Barelang road. The location of the existing TPS on Pulau Setokok is not in the recommended TPA location based on SNI No.19-3241-1994. The length of time for transporting waste using a Dump Truck is 108.6 minutes which is faster than an Arm Roll Truck (173 minutes) for round-trip waste transportation from TPA Punggur – TPA Recommendation of Pulau Setokok – TPA Punggur on the shortest route of 2 times 36.2 km. the use of Arm Roll Truck fuel is more efficient, which is Rp 93,637.33 for 1 trip compared to the Dump Truck (Rp 117,046.67), but the Arm Roll Truck transports less waste than the Dump Truck because of its smaller capacity, which is 7.2 m3 compared to the Dump Trucks of 12 m3.